Highly diastereoselective synthesis of enantioenriched: Anti -α-allyl-β-fluoroamines - Philip J. Chevis (2019)
© 2019 The Royal Society of Chemistry. A highly diastereoselective synthesis of anti-α-allyl-β-fluoroamines has been developed involving enantioselective α-fluorination of aldehydes followed by a diastereoselective Petasis allyl borono-Mannich reaction. The products are obtained generally in good overall yields for the two steps and with drs of 97:3-99:1 and ees of 86-92%. Selected products were converted to 3-, 5- and 6-membered ring heterocycles, the latter two types incorporating an exo-cyclic fluorine.